The role of hydrophilic implant surfaces to enhance the osseointegration process: Peran permukaan implan yang hidrofilik untuk meningkatkan proses osseointegrasi - Irfan Dammar; Fitrian Riksavianti; Eri Hendra Jubhari (Makassar Dental Journal, 2024)
The hydrophilic surface of the implant is one of the factors to improve the stimulation of osseointegration. Modification of the im-plant surface has been done through increasing wettability to improve oseointegration and accelerate the healing time period. Protein adsorption and blood coagulation play an important role in the early stages of oseointegration and are strongly influenced by implant surface properties. This article reviews the literature on the effect of hydrophilic implant surface properties to improve the process of oseointegration. Literature searches were conducted using PubMed, Science Direct and Google Scholar. Hydrophi-lic implant surfaces modulate osteogenic gene expression at the healing site and stimulate osteoblasts. In the exudative phase, the hydrophilic implant surface interacts with water molecules and ions to better maintain protein conformation and function. In the inflammatory phase the hydrophilic implant allows fibroblast attachment to integrin binding regions. In the proliferation phase osteoprogenitor cells attach to the implant surface stimulating fibronectin formation. It is concluded that the wettability of the hy-drophilic implant surface is essential to improve osseointegration and accelerate the healing time period.